The Top 10 fungal pathogens in molecular plant pathology - DEAN, RALPH; VAN KAN, JAN A. L.; PRETORIUS, ZACHARIAS A.; HAMMOND-KOSACK, KIM E.; DI PIETRO, ANTONIO; SPANU, PIETRO D.; RUDD, JASON J.; DICKMAN, MARTY; KAHMANN, REGINE; ELLIS, JEFF; FOSTER, GARY D. (Molecular plant pathology, 2012)
SUMMARY The aim of this review was to survey all fungal pathologists with an association with the journal Molecular Plant Pathology and ask them to nominate which fungal pathogens they would place in a ‘Top 10’ based on scientific/economic importance. The survey generated 495 votes from the international community, and resulted in the generation of a Top 10 fungal plant pathogen list for Molecular Plant Pathology. The Top 10 list includes, in rank order, (1) Magnaporthe oryzae; (2) Botrytis cinerea; (3) Puccinia spp.; (4) Fusarium graminearum; (5) Fusarium oxysporum; (6) Blumeria graminis; (7) Mycosphaerella graminicola; (8) Colletotrichum spp.; (9) Ustilago maydis; (10) Melampsora lini, with honourable mentions for fungi just missing out on the Top 10, including Phakopsora pachyrhizi and Rhizoctonia solani. This article presents a short resumé of each fungus in the Top 10 list and its importance, with the intent of initiating discussion and debate amongst the plant mycology community, as well as laying down a bench‐mark. It will be interesting to see in future years how perceptions change and what fungi will comprise any future Top 10.